(untitled) (Journal of Advanced Veterinary and Animal Research, 2020)
Objectives: The present study estimated the seroprevalence of avian reovirus (ARV) infections in backyard chickens of the Mymensingh district in Bangladesh. Materials and Methods: Considering several risk factors, a total of 460 serum samples were collected from backyard chickens from eight Upazilas of the Mymensingh district in Bangladesh. Blood samples were taken from the wing vein using 3-ml sterile syringes and kept at room temperature for clotting in a slanting position and then transported to the laboratory maintaining the cool chain. Subsequently, the prepared sera were harvested and stored at −20°C until used. Finally, an indirect enzyme-linked immunosorbent assay (ELISA) was performed to detect ARV-specific antibodies using a commercial ARV antibody detection ELISA test kit. Results: The results revealed high prevalence rates of ARV antibodies, with a total seroprevalence of 69.78% (321/460). Area-wise, 74.55% (82/110) seroprevalence was recorded as the highest in Mymensingh Sadar, whereas 64% (32/50) was the lowest in Gauripur Upazila. With regard to sex, female chickens showed a significantly higher (p < 0.05) seroprevalence as 90.33% (271/300) compared to male chickens 31.25% (50/160). With regard to age groups, the seroprevalence of ARV infection was 59.33% (89/150) within 2–8 weeks, 82% (205/250) within 9–16 weeks, and 45% (27/60) within 17–20 weeks, respectively. Based on hygienic conditions, the highest seroprevalence of ARV was noted in backyard chickens housed in poor conditions 80% (120/150) than good conditions 50% (40/80). Backyard chickens reared in free-ranging conditions exhibited a significantly higher seroprevalence 73.33% (220/300) of ARV antibodies compared to rearing in separate houses 63.12% (101/160). The seroprevalence of ARV was higher in crossbreeds 71.67% (43/60), brought from market 76% (38/50), and unhealthy 78.57% (55/70) backyard chickens than non-descriptive indigenous 69.5% (278/400), home-reared 69.02% (283/410), and healthy chickens 68.21% (266/390). Conclusion: The high prevalence of ARV antibodies revealed in the current study indicates an extensive exposure of ARV to backyard chickens in Bangladesh that may be transmitted naturally to other chickens, ultimately leading to ominous economic effects on the poultry sector. J. Adv. Vet. Anim. Res., 7(3): 546-553, Sep 2020 http://doi.org/10.5455/javar.2020.g452